PENGARUH VARIASI MAIN JET NOZZEL PADA SISTEM KARBURATOR TERHADAP UNJUK KERJA MESIN (Studi Kasus Beberapa Tingkat Oktan) - Charlie Christian (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: This study discusses the effect of variations in the diameter of the main jet nozzle and three types of fuel with an octane rating of 88, 90 and 92 on the performance of the motor fuel. Performance analysis covering torque, power and specific fuel consumption (SFC). In order to determine the maximum performance that can be generated on any variation of the diameter of the main jet nozzles, and types of fuel. At the time of this experiment performed with a 4 stroke engine Honda GX-160, using hydro tool dynamometer and uses premium fuel. The data taken is the engine rotation, the force measured on the dynamometer and the time spent fuels. Tests conducted at the Laboratory of Energy Conversion Mechanical Engineering UNTAR Jakarta. Testing is done by means of rotational load mengvariasikan to gain strength in each round machine with a variety of major diameter nozzle jet fuel and octane. Variation of the engine rotation starts at minimal rotation until maximum.